Combustion LES for premixed and diffusion flames. (19th July 2005) - Dusing, Michael; Kempf, Andreas; Flemming, Felix; Sadiki, Amsini; , Johannes Janicka
This paper demonstrates the ability of large-eddy simulation (LES) to accurately predict turbulent combustion. A non-premixed bluff-body flame was simulated, relying on the conserved scalar approach and the laminar flamelet concept. The results were found to agree well with experimental data. A premixed flame, stabilised behind a rearward-facing step, was investigated with LES and a filtered G-equation model. The results were compared to experimental data to assess the accuracy of the approach. The filtered G-equation model was chosen based on the generalised regime diagram for turbulent combustion, which considers the influence of the LES filter width. A combination of both simulation methods introduced here gives the possibility to simulate partially premixed combustion.